2018
DOI: 10.1101/286351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling of pluripotency factors in individual stem cells and early embryos

Abstract: Major cell fate decisions are governed by sequence-specific transcription factors (TFs) that act in small cell populations within developing embryos. To understand how TFs regulate cell fate it is important to identify their genomic binding sites in these populations. However, current methods cannot profile TFs genome-wide at or near the single cell level. Here we adapt the CUT&RUN method to profile chromatin proteins in low cell numbers, mapping TF-DNA interactions in single cells and individual pre-implantat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…ChIP requires substantial cellular material, limiting its application for experimental and clinical samples. However, we and others have previously demonstrated that tethered profiling strategies like CUT&RUN have sufficient sensitivity that profiling small cell numbers routinely becomes feasible 9,24 . Signal improvements in CUT&Tag suggest that this method may work even more efficiently with limited samples.…”
Section: Cutandtag Profiles Low Cell Number Samples and Single Cellsmentioning
confidence: 98%
“…ChIP requires substantial cellular material, limiting its application for experimental and clinical samples. However, we and others have previously demonstrated that tethered profiling strategies like CUT&RUN have sufficient sensitivity that profiling small cell numbers routinely becomes feasible 9,24 . Signal improvements in CUT&Tag suggest that this method may work even more efficiently with limited samples.…”
Section: Cutandtag Profiles Low Cell Number Samples and Single Cellsmentioning
confidence: 98%
“…The performance of cisTopic was confirmed on simulated H3K27Ac ChIP-seq data, which we believe 482 represents a relevant test case, given that the recently developed single-cell CUT&RUN (an alternative 483 to ChIP-seq to profile TF binding or histone modifications in single cells) will likely be widely adopted 484 (Hainer et al, 2018). Our results on 14 melanoma cell lines showed that cell clustering is 96% accurate 485 even with as few as 3,000 reads per cell.…”
mentioning
confidence: 58%
“…Although single-cell transcriptomics allows an unbiased detection of cellular diversity, 33 reverse engineering the genomic regulatory code from the transcriptome remains a challenge. On the 34 other hand, single-cell epigenomic techniques, such as single-cell ATAC-seq (scATAC-seq) 35 (Buenrostro et al, 2015;Cusanovich et al, 2015), single-cell CUT&RUN (Hainer et al, 2018), or 36 single-cell DNA methylome sequencing (Farlik et al, 2015), provide a more direct prediction of the 37 genome-wide activity of enhancers and promoters, at single-cell resolution. These approaches, in 38 particular single-cell chromatin accessibility profiling using scATAC-seq, allow the discovery of 39 multiple cell types and regulatory states from a heterogeneous mixture of cells, such as a whole 40 organism (Cusanovich et al, 2018), a whole organ (Lake et al, 2017), or an asynchronous dynamic 41 process like differentiation (Corces et al, 2016;Pliner et al, 2017).…”
Section: Introduction 27mentioning
confidence: 99%
“…Other advances based on our original CUT&RUN publication include CUT&RUN.Salt for fractionation of chromatin based on solubility (16) and CUT&RUN.ChIP for profiling specific protein components within complexes released by CUT&RUN digestion (17). CUT&RUN has also been adopted by others (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and since publication of our eLife paper we have distributed materials to >500 laboratories world-wide, with user questions and answers fielded interactively on our openaccess Protocols.io site (31).…”
Section: Introductionmentioning
confidence: 99%